History of memory and the memory of history: the case of Mustapha Bekkouche - Aissani , Redouane (Journal of Human Sciences, 2022)
The interweaving of fiction and History generates aesthetic issues that engage the writer in paths of a singular writing. The work is then permeated on all sides by historical references revealing a clear determination on the part of the author to grind the silences, falsifications and grey areas of the official history.In Mustapha Bekkouche's work, reality no longer appears as an acquired datum but rather as a fact that remains to be conquered and even to be reclaimed. From this perspective, the notions of fiction and reality no longer belong to the order of the discontinuous, but of a continuum. Through its almost obsessive anchoring in the history of Algeria, the author's work pursues a meta discursive strategy which aims at the subversion of historical reality